Randomized, double-blind, comparative-effectiveness study comparing pulsed radiofrequency to steroid injections for occipital neuralgia or migraine with occipital nerve tenderness. Issue 12 (December 2015) - Cohen, Steven P.; Peterlin, B. Lee; Fulton, Larry; Neely, Edward T.; Kurihara, Connie; Gupta, Anita; Mali, Jimmy; Fu, Diana C.; Jacobs, Michael B.; Plunkett, Anthony R.; Verdun, Aubrey J.; Stojanovic, Milan P.; et al.
Abstract : Abstract: Occipital neuralgia (ON) is characterized by lancinating pain and tenderness overlying the occipital nerves. Both steroid injections and pulsed radiofrequency (PRF) are used to treat ON, but few clinical trials have evaluated efficacy, and no study has compared treatments. We performed a multicenter, randomized, double-blind, comparative-effectiveness study in 81 participants with ON or migraine with occipital nerve tenderness whose aim was to determine which treatment is superior. Forty-two participants were randomized to receive local anesthetic and saline, and three 120 second cycles of PRF per targeted nerve, and 39 were randomized to receive local anesthetic mixed with deposteroid and 3 rounds of sham PRF. Patients, treating physicians, and evaluators were blinded to interventions. The PRF group experienced a greater reduction in the primary outcome measure, average occipital pain at 6 weeks (mean change from baseline −2.743 ± 2.487 vs −1.377 ± 1.970; P < 0.001), than the steroid group, which persisted through the 6-month follow-up. Comparable benefits favoring PRF were obtained for worst occipital pain through 3 months (mean change from baseline −1.925 ± 3.204 vs −0.541 ± 2.644; P = 0.043), and average overall headache pain through 6 weeks (mean change from baseline −2.738 ± 2.753 vs −1.120 ± 2.1; P = 0.037). Adverse events were similar between groups, and few significant differences were noted for nonpain outcomes. We conclude that although PRF can provide greater pain relief for ON and migraine with occipital nerve tenderness than steroid injections, the superior analgesia may not be accompanied by comparable improvement on other outcome measures. Abstract : In this double-blind, multicenter, comparative-effectiveness study, we found that pulsed radiofrequency provided better pain relief than steroid injections in patients with occipital neuralgia.